Genomic Instability and Cancer: Lessons Learned from Human Papillomaviruses - Korzeniewski, Nina (2010)
High-risk HPV E6 and E7 oncoproteins cooperate to subvert critical host cell cycle checkpoint control mechanisms in order to promote viral genome replication. This results not only in aberrant proliferation but also in host cellular changes that can promote genomic instability. The HPV-16 E7 oncoprotein was found to induce centrosome abnormalities thereby disrupting mitotic fidelity and increasing the risk for chromosome missegregation and aneuploidy. In addition, expression of the high-risk HPV E7 oncoprotein stimulates DNA replication stress as a potential source of DNA breakage and structural chromosomal instability. Proliferation of genomically unstable cells is sustained by several mechanisms including the accelerated degradation of claspin by HPV-16 E7 and the degradation of p53 by the high-risk HPV E6 oncoprotein. These results highlight the oncogenic potential of aberrant proliferation and opens new avenues for prevention of malignant progression, not only in HPV-associated cervical cancer but also in non-virally associated malignancies with disrupted cell cycle checkpoint control mechanisms.